Traumatic oculomotor nerve palsy treated with transnasal endoscopic decompression through the optic strut - Wang, Anqi; Wang, Mian; Wu, Yanqiao; Zhao, Yifan; Wang, Zhimin; Shen, Likui (Frontiers in Surgery, 2023)
Objective: To present a surgical treatment regimen of nasal endoscopic decompression through the optic strut for traumatic oculomotor nerve palsy based on the anatomical study of the superior orbital fissure and the oculomotor nerve fissure segment. Methods: The bone structure of the oculomotor nerve fissure segment and the important bone anatomical landmarks of the lateral wall of the sphenoidal sinus were identified on a dried skull and a cadaveric head, respectively, using a nasal endoscope, and a surgical plan was determined. Decompression was conducted on the orbital apex, the superior orbital fissure, the optic canal and the optic strut of the two patients in sequence, after which the degree and range of decompression were identified by three-dimensional (3D) computed tomography (CT). Results: The oculomotor nerve had a close correlation with the lateral surface of the optic strut. The nasal endoscope was employed to identify the optic-carotid recess (OCR), as well as the positions of the optic nerve, internal carotid artery (ICA), and superior orbital fissure, collectively called the "optic strut triangle". The surgical plans for decompression of the orbital apex, superior orbital fissure, optic canal, and optic strut and the necessity of optic strut grinding were determined, and the surgical procedures for safe grinding of the optic strut were elaborated. After surgery, the two patients had significantly improved symptoms, without complications. In addition, their postoperative CT showed that the medial margin of the superior orbital fissure was fully decompressed. Conclusion: The optic strut triangle is a crucial anatomical landmark in the decompression of the oculomotor nerve, and optic strut grinding is necessary for such decompression. For patients with traumatic oculomotor nerve palsy and fractures of the medial wall of the superior orbital fissure on CT, the oculomotor nerve fissure segment can be decompressed in an effective, complete and safe manner as per the surgical plan of decompressing the orbital apex, superior orbital fissure, optic canal and optic strut in turn under a nasal endoscope, conducive to the recovery of neurological function of patients.